2013
DOI: 10.1111/cas.12287
|View full text |Cite
|
Sign up to set email alerts
|

P16INK4A as a surrogate biomarker for human papillomavirus‐associated oropharyngeal carcinoma: Consideration of some aspects

Abstract: Human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinomas (OPSCCs) frequently show different clinical and pathological features, which tend to be younger age, better performance status, less tobacco and alcohol consumption, more poorly differentiated histopathology, but usually with better treatment response and prognosis compared with HPV-negative OPSCCs. In tumor tissue, HPV infection is closely correlated with p16INK4A expression, which has been suggested to be a surrogate biomarker of HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…By naked eye visualization, the all three dyes demonstrated similar sensitivities, in which the detection limit was 10 3 copies/μl of HPV16. Our findings are in agreement with the previous studies, which reported no differences observed when different dyes were used for naked eye detection of LAMP products (Kwok & Kwong 2013;Wang et al 2013). Agarose gel electrophoresis and real-time analysis demonstrated the same detection limit as naked eye detection (10 3 copies/μl of HPV16).…”
Section: Discussionsupporting
confidence: 92%
“…By naked eye visualization, the all three dyes demonstrated similar sensitivities, in which the detection limit was 10 3 copies/μl of HPV16. Our findings are in agreement with the previous studies, which reported no differences observed when different dyes were used for naked eye detection of LAMP products (Kwok & Kwong 2013;Wang et al 2013). Agarose gel electrophoresis and real-time analysis demonstrated the same detection limit as naked eye detection (10 3 copies/μl of HPV16).…”
Section: Discussionsupporting
confidence: 92%
“…Although excellent concordance between HPV DNA status and p16 ink4 immunoreactivity was observed, three out of 11 HPV-negative cases (27%) strongly expressed this surrogate biomarker for HPV infection. This phenomenon of false-positive results with the use of p16 ink4 immunostaining has been extensively reported in the context of head and neck cancers [38]. Although less frequently detected, similar data were also recently pointed out in anal SCC [9,10].…”
Section: Herfs Et Alsupporting
confidence: 72%
“…INK4a is inexpensive, highly sensitive and can be performed in virtually any histology laboratory with very quick turnaround (34,46).…”
Section: Immunohistochemistry (Ihc) For P16mentioning
confidence: 99%
“…INK4a is often used as a surrogate marker of HPV infection in oropharyngeal cancers, while its use in oral cavity cancers is not well established, even though both are subgroups of HNC (46,47). Current studies show that other non-viral mechanism can also increase p16 INK4a expression, making it a non-specific marker for HPV infection, Figure 5 (18,46,48).…”
Section: Overexpression Of P16mentioning
confidence: 99%
See 1 more Smart Citation